(intelligent thinking among middle school students ) (Journal of the College of Basic Education, 2025)
The current research aims to:1- Identifying clever thinking among middle school students.2-The significance of the differences in clever thinking according to the variable of specialization (scientific, literary).The researcher adopted the scale (Al-Saadi 2013) prepared for the purpose of preparing items for the clever thinking scale according to the theoretical definition adopted by Costa and Kalick (Costa & Kalick, 2005) using the method of five-graded declarative statements and extracting the psychometric properties represented by validity (discriminatory power, internal consistency and reliability using the retest method and The (Cronbach's alpha) equation and the statistical indicators of the scale, verifying the first objective using the t-test for one sample, and verifying the second objective using the t-test for two independent samples of different numbers.The researcher reached the following results:The members of the current research sample have a high level of clever thinking.There are no statistically significant differences in clever thinking according to the specialization variable (scientific, literary).To complement the current research, the researcher presented a number of recommendations and suggestions.